Addition of an approach to a relay start - McLean, S. P.; Holthe, M. J.; Vint, P. F.; Beckett, K. D.; Hinrichs, R. N. (Journal of Applied Biomechanics, 2000)
Summary This study was designed to examine differences between commonly used relay starts. More and more, we see athletes deviate from the "traditional" relay start and introduce an approach, or stepping motion, into the start. The question arises as to whether this stepping action actually helps the athlete have a faster start. The investigators chose to examine four different types of starts: - The traditional relay start with no steps - Single step-start, beginning with the feet in a track start position - Single step-start, beginning with the feet together at the back of the blocks - Double step-start, beginning with the feet together at the back of the blocks The study chose to examine numerous variables associated with movements incorporated in the start like take-off and entry angles, and velocities in the horizontal and vertical directions at take-off. Probably the most important variable that was measured, however, was the time it took the athlete to reach the 10-meter mark. It is important to note that all athletes used in this study were collegiate male swimmers (n=10) who spent 6 hours practicing the different starts over a 12 week period leading up to the testing. Findings None of the "step-starts" resulted in a significantly faster time to 10 meters when compared to the traditional start. For the double-step start, significant changes were seen in velocity at takeoff and entry (both higher than seen in the traditional start). For the single-step start, beginning with the feet together at the back of the blocks, significant changes were seen in the vertical takeoff velocity (lower), the takeoff angle (lower), velocity at entry (higher) and entry angle (higher) when compared to the traditional start. This looked to be a "flatter" start at takeoff, with a slightly "steeper" entry. There are still many unknowns when it comes to determining what makes a fast relay start. Implications The findings of this study suggest that there is no significant performance improvement when "steps" are introduced into a relay start. In fact there were not even any trends toward better performance when the steps were introduced into the starts. While small changes were seen in the way the swimmers left the blocks and entered the water, they did not translate to any improvements in time to the 10 meter mark. Traditional relay starts appear to be just as effective as the step starts.